Keefektifan model pembelajaran berbasis proyek dalam kurikulum merdeka terhadap kemampuan pemecahan masalah siswa kelas IX - Hasanah, Risqan; Sari, Dwi Ivayana (Papanda Journal of Mathematics and Science Research, 2025)
Mathematics plays a significant role in developing students' logical, critical and creative thinking abilities. However, there are still many students who consider mathematics to be a difficult subject, which ultimately influences students' low ability to solve problems. This research aims to determine the effectiveness of the project-based learning model in the independent curriculum on students' problem-solving abilities. This research design uses Pretest-Posttest Control Group Design. The data analysis technique in this research uses statistical test analysis. The type of research used is quantitative research. The sample used was class IX of Ibnu Umar Geger, Bangkalan, Indonesia Middle School. The instruments used include the teacher's ability to manage learning, student activities, student responses and pretest-posttest score results. Based on the results of data analysis, it shows that the average score for teachers' ability to manage learning using the Project Based Learning learning model was obtained at 4 (very good category). Thus, the teacher's ability to manage learning is said to be effective. Data analysis of the percentage of student activity towards the Project Based Learning learning model was obtained at 3.75 (very active category), and students' positive response to the Project Based Learning learning model was obtained at 93% ((strongly agree category) students felt happy following the Project Based Learning learning model. Thus the student response was said to be effective. Descriptive analysis of the pretest and posttest scores used data normality tests and hypothesis testing. The project based learning model can be said to be effective in improving students’ problem solving abilities. This research has had a positive impact on improving students' abilities, particularly in problem-solving, critical thinking, and active participation during the learning process. Overall, the findings of this study contribute to the development of innovations in mathematics learning. The applied learning model can be used by educators as a more engaging teaching method and one that actively engages students.